Efektivitas Penegakan Hukum Pajak Kendaraan Bermotor: Analisis Pengaruh Surat Teguran, Keadilan Prosedural, dan Kesadaran Hukum terhadap Tingkat Kepatuhan Wajib Pajak di SAMSAT Kabupaten Sumbawa - Riska Ayu Purnama Dewi; Reza Muhammad Rizqi (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to evaluate the effectiveness of motor vehicle tax law enforcement by analyzing the impact of warning letters, procedural justice, and legal awareness on taxpayer compliance at the Joint Office of SAMSAT in Sumbawa Regency, Indonesia. Grounded in the Deterrence Theory and the Slippery Slope Framework, this research addresses the persistent gap between regional tax potential and actual revenue realization caused by recurring administrative non-compliance. A quantitative research design was strictly employed, utilizing primary data collected through purposively distributed questionnaires to 94 registered motor vehicle taxpayers. The empirical data were subsequently analyzed using multiple linear regression, systematically preceded by classical assumption tests to ensure model validity. The statistical findings reveal that simultaneously, the issuance of warning letters, perceived procedural justice, and legal awareness significantly influence overall tax compliance. However, partial hypothesis testing demonstrates a decidedly contrasting outcome: only the effectiveness of warning letters yields a positive and highly significant impact on taxpayer compliance. In contrast, both procedural justice and legal awareness fail to exhibit any statistically significant effect. These empirical results robustly conclude that active tax collection through formal administrative reprimands serves as the predominant catalyst for tax discipline within this specific regional demographic, significantly overshadowing internal moral drivers. Consequently, local tax authorities must continuously prioritize rigorous law enforcement and active billing mechanisms to sustainably optimize regional original revenue.